Pengembangan REST API dengan menggunakan Express JS untuk mencari Mentor Pribadi - Nasrul Nasrul; Achmad Izhar (Jurnal Informatika Terpadu, 2023)
Currently there is a problem faced by many students, namely in understanding and mastering programming. These problems occur due to limitations in understanding program code, limited access to learning media, and limited learning time. To answer this challenge, the design and development of the Rest API for finding personal mentors is proposed as a solution that can improve the quality and effectiveness of learning program code. In this research, the Express JS framework is used to implement the Rest API, which interacts with third party APIs such as Midtrans and Redis. The MVC development approach and the Scrum method are applied to manage the application development process. The aim of this research is to design and build a Rest API that allows students to find a personal mentor that suits their needs in learning code. It is hoped that the use of Express JS and the Scrum method in the development of this application will facilitate the creation of effective and efficient private coding applications.